Assessing organizational ethics through stakeholders democracy (participation and dialogue) the case of the Philippine-Japan active carbon corporation - Cirunay, Sonny Paul R.
Organizational goals often take precedence over interests of its stakeholders, most especially those of workers who are at the bottom of the organizational hierarchy. Organizational ethics (Phillips, 2003) is now grounded on fair play focusing on the organization?s ethical obligation to gratify stakeholders by responding to their needs in accordance to the benefits the organization gets out of their cooperation. Stakeholders must be able to identify their interests, implying the obligation for open communication through the principles of participation and dialogue that promote stakeholder democracy, which can ideally be practiced through Collective Bargaining Agreements. This study was conducted to determine the extent by which the communicative principles of participation and dialogue were practiced in the conduct of the CBA negotiations of the Philippine-Japan Active Carbon Corporation (PJAC). This is a unique case since PJAC runs negotiations for CBA without the presence or intervention of legal counsels. This practice started in 2007. The study analyzed the minutes of CBA negotiations, in-depth key informant interviews and focused group discussion with workers within the organization using the model participation from the Critical Theory of Communication Approach to Organizations and the concepts from the Coordinated Management of Meaning for dialogue. The results of the study revealed that the workers of PJAC were able to freely form and express their interests and concerns to the management. During negotiations, dialogue was evident. Co-contribution of symbols, stories and information was done and creation of organizational reality was co-constructed with the stakeholders during the deliberation. There was the presence of the given mechanisms within the negotiation process such as the absence of legal counsels, the non-involvement of any third party, and ground rules adopted in the negotiations that facilitated explorations through dialogue and participation. The study is able to establish that participation and dialogue not only promoted fair play through stakeholders democracy but also allowed parties a greater opportunity to discuss ethics within the workplace which usually isn?t carried out under normal conditions. The results of this study may be used to improve managerial practices within organizations.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication